Problems & solutions in scientific computing : with C++ and Java simulations - Steeb, Willi-Hans (Hackensack : World Scientific, 2004)
Many problems include software simulations. Algorithms have detailed implementations in C++ or Java. This book should prove to be useful not only to students and research workers in the fields of scientific computing, but also to teachers of this subject who will find this text useful as a supplement.
Includes bibliographical references (p. 413-416) and index.
Keywords: Numerical analysis -- Computer programs -- Problems, exercises, etc..; Science -- Mathematics -- Computer programs -- Problems, exercises, etc..